A Digital Comic-Based Approach to Cyberbullying Prevention for Improving Internet Safety Among Elementary School Students - Syarifah Fadillah Rezky; Siti Julianita Siregar; Rita Hamdani; Meri Sri Wahyuni (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2026)
Background: The rapid growth of digital technology use among elementary school students has increased their exposure to cyberbullying and unsafe online behavior. Preliminary observations conducted at Sekolah Anak Tangguh an Nuha identified several challenges, including limited digital literacy awareness, insufficient interactive learning media, and a lack of understanding regarding cyberbullying prevention among students. Contribution: This community service program introduces a digital comic-based educational intervention that integrates visual storytelling, digital ethics, and participatory learning activities to enhance students’ awareness of cyberbullying and responsible internet use. The program offers an innovative approach by combining contextual digital narratives with interactive classroom engagement specifically designed for elementary school students. Method: The program employed a participatory community service method with an educational intervention approach involving 35 elementary school students. The implementation stages included needs assessment, digital comic development, guided learning activities, mentoring sessions, and evaluation through pre-test and post-test assessments, observations, and questionnaires. Results: The findings revealed a significant improvement in students’ understanding of cyberbullying following the intervention. The proportion of students categorized at the high understanding level increased from 20.0% to 60.0%, while the percentage of students in the low understanding category decreased from 42.9% to 11.4%. In addition, students demonstrated greater engagement and more active participation throughout the learning activities. Conclusion: Digital comic-based learning represents an effective and engaging approach for strengthening digital literacy and cyberbullying awareness among elementary school students.